Comparative analysis between GCS (Glasgow coma scale) and FOUR (Full Outline of Unresponsiveness) score in preliminary assessment and prognostication of traumatic brain injury - Keerthi, Sri; Doshi, Anand; Doshi, Rajeev; Khandelwal, Prashant; Ketkar, Mrunal; Sudambrekar, Sudhir (Nepal Journal of Neuroscience, 2023)
Introduction: Head injury is one of the most critical conditions and has a serious neurological outcome if not treated promptly. Effective initial assessment and timely intervention ensures a favourable outcome. To achieve this, many assessment scoring systems have been devised over the years of which Glasgow coma scale (GCS) is the most widely used but it does have a few drawbacks. A newer coma scale, the FOUR score (Full Outline of UnResponsiveness) evaluates four components. The aim of the present study is to compare the GCS and FOUR score in traumatic head injury patients in predicting the better outcome. The outcome scoring is done by GCOS (Glasgow Coma Outcome Scale). Methods and Materials: One twenty-five patients with traumatic head injury were recruited between September 2019 to September 2021 in a tertiary health care centre. For all these cases, GCS and FOUR score on the day of arrival in emergency department (ED) was calculated by residents attending the case in ED and the outcome was scored using GCOS. The correlation between all three scores was then calculated. Results: The present study revealed the major cause of traumatic head injury as road traffic accidents and most of them being males. A significant strong positive correlation was found in FOUR score when compared with GCS in the prediction of outcome in traumatic brain injury patients. Conclusion: It was concluded that the FOUR score is more beneficial to that of GCS and can be used in outcome assessment in traumatic head injury and intubated patients. Thus, FOUR score is a better tool for prognostication.